Upaya meningkatkan hasil belajar matematika peserta didik melalui model pembelajaran discovery learning - Ashabulabib, Adib; Suparni; Suryantana (Pusat Studi Pengembangan Pembelajaran Matematika, 2025)
Mathematics learning plays a crucial role in developing students' logical and analytical thinking skills. The 2022 PISA results indicate that Indonesia still lags in mathematical proficiency, partly due to the use of less innovative teaching methods. This study aims to determine the effectiveness of the Discovery Learning model in improving students' mathematics learning outcomes. The research method employed was classroom action research using Ernest T. Stringer's model, which consists of the Look, Think, and Act stages. The study was conducted in class X E at MAN 2 Bantul with 36 students. The results showed a significant improvement in learning outcomes after the implementation of Discovery Learning, with the average score increasing from 65.81 to 81.53 and the completion rate rising from 39% to 81%. The analysis using the Paired Sample t-Test indicated a significance value of 0.000 < 0.05, confirming that Discovery Learning is effective in enhancing learning outcomes. The implications of this study suggest that the Discovery Learning model can serve as an alternative to enhance student engagement and understanding in mathematics learning. Educators are encouraged to implement this method more broadly and receive support from schools in providing interactive learning media and relevant training.